Phytoremediation of heavy metals and nutrients by the Sagittaria montevidensis into an anthropogenic contaminated site at Southern of Brazil. Issue 11 (19th September 2019) - Demarco, Carolina Faccio; Afonso, Thays França; Pieniz, Simone; Quadro, Maurízio Silveira; Camargo, Flávio Anastácio de Oliveira; Andreazza, Robson
Abstract: The evaluation of plants occurring naturally at contaminated environments are essential for applying this species in remediation techniques. In this context, the Sagittaria montevidensis with potential for phytoremediation was studied at an anthropogenic polluted stream in southern Brazil. The nutrients and heavy metal content were determined in the phytomass. The phytoremediation indexes were evaluated such as bioconcentration factor (BCF), translocation factor (TF), plant effective number (PEN), and potential phytoremoval (mg m −2 ). The S. montevidensis was then detected as presenting natural phytoextraction ability for potassium and calcium elements and also demonstrated rhizofiltration potential for phosphorus, manganese, aluminum, vanadium, sulfur, iron, arsenic, copper, magnesium, zinc, sodium, lead, cadmium, nickel, chromium, considering its ability of bioaccumulating these contaminants and retain high levels in the roots. The highest potential for bioremoval (mg m −2 ) of the S. montevidensis was detected for potassium and calcium (recommending thus the use for phytoextraction) and for aluminum, phosphorus, iron, magnesium, sulfur, and sodium, along with heavy metals (recommended for rhizofiltration). The S. montevidensis decontamination ability, along with its biomass production and its adaptability represents a great advance in order to the recovery of this degraded area and possible application in other contaminated watercourses in Brazil.